"The Enemy - A Partisan Hymnbook" - Critical Notes on Memory, Music, and the Making of a Documentary Film - Spinetti, Federico (’’Music in Society’’ The Collection of Papers, 2020)
In the following pages I provide a study guide and a critical discussion of my documentary film The Enemy – A Partisan Hymnbook (2015). In the process, my reflexive and interpretive remarks are meant to bear on issues of more general interest for the study of music, memory and conflict, and for the theory and practice of audio-visual media particularly in ethnomusicology.